Intraoperative electro-oculographic Monitoring for Skull Base Surgery - Fukaya, Chikashi (2000)
During surgery on the skull base, preservation of the integrity of the ocular motor nerves is vitally important. Intraoperative electrophysiological monitoring methods for protecting such functions have been reported by several investigators. However, these methods so far have not been popularized sufficiently, due to the difficulty and complexity of the procedures involved. The authors have developed an extremely simple but far more reliable method using electro-oculography under total intravenous anesthesia with propofol to preserve the integrity of the ocular motor nerves. The ocular motor nerves were stimulated with a monopolar electrode intracranially, and the polarity of the waves was recorded using surface electrodes placed around the eyeball, yielding precise information concerning the locations of the oculomotor nerve and/or abducent nerve. In addition, by performing continuous monitoring, invasive procedures affecting the ocular motor nerves could be detected as spontaneous ocular movements. In practice at our department, this method has been applied in 12 cases with tumors close to the ocular motor nerves, and has produced excellent results.